Defining forms of public space: a frame for understanding 'the Vatican's economic reform' - Mendoza, Cristian (Church, Communication and Culture, 2016)
This article aims to construct a frame for the sake of understanding why the Vatican's economic reform is so often called into question in the public space. For present purposes, the public space must be distinguished according to the differing forms in which it manifests itself: democratic movements, social initiatives and the mechanisms of the free market economy. With respect to the latter form, the Vatican economic reform is observed and judged by the Church's different publics, for instance, her faithful, her international financial regulators and governmental organizations. The frame here established allows an analysis of some of Pope Francis' most important decisions regarding 'the Vatican's economic reform'. These decisions have neither been simply the fruit of the Holy Father's desire to change the Roman Curia's administration, nor have they been solely dependent on pressure from international regulation offices. The Vatican accepted external requirements in order to preserve its institutional mission, which is primarily a spiritual mission in service to its faithful all around the world. Pope Francis' leadership is not only rooted in his authenticity, being himself extremely attractive to the media, but also in his credibility, being a pastor with the capacity to change the institution from within. These two characteristics, falling within the categories of transparency and reform, are greatly appreciated in the public space.